THE FACTORS THAT INFLUENCE THE FAILURE OF SIMANTRI PROGRAM IN REALIZING SUSTAINABLE AGRICULTURE - Luh Putu Kirana Pratiwi; Made Budiasa; Ni Made Kencana Maharani (International Journal of Applied Science and Sustainable Development (IJASSD), 2021)
The Integrated Agricultural System is one of the flagship programs of the Bali Provincial Government as a breakthrough effort to accelerate the adoption of agricultural technology in supporting the development of agricultural diversification in an integrated manner and with an agribusiness perspective. The development model is oriented towards the concept of zero waste production system. This program encountered various obstacles, that based on the 96 Integrated Agricultural System Groups active in Bangli Regency that it was not fully able to increase income significantly. In this study the factors that influence the failure of the Integrated Agricultural System Program in realizing sustainable agriculture are twelve factors, namely companion performance, accessibility, communication, effectiveness, coordination, transparency, technology adoption, social capital, group participation, increased income, institutional and, efficiency. It is hoped that the evaluation of the Integrated Agricultural System Program in the entire Province of Bali will be able to improve system performance so that in the future it can be a driving force in economic development.